Using Aliphatic Alcohols to Tune Benzene Adsorption in MAF‐6. Issue 11 (5th August 2019) - Martin‐Calvo, Ana; Gutierrez‐Sevillano, Juan Jose; Dubbeldam, David; Calero, Sofia
Abstract: This simulation study deals with benzene adsorption in the metal azolate framework, MAF‐6, and on the inversion of the adsorption behavior in presence of aliphatic alcohols with varying chain length. To this aim, a new set of Lennard‐Jones interacting parameters for the MAF structure with benzene, methanol, ethanol, and 1‐propanol is developed in order to reproduce experimental adsorption. Pure component and binary benzene/alcohol mixtures are analyzed using Monte Carlo simulations. The distribution of the molecules inside the structure is studied in terms of radial distribution functions, calculated to understand the adsorption mechanisms. Adsorption selectivity provides a better understanding of the effect exerted by the adsorption of alcohols. It is found that the adsorption of benzene from benzene/methanol mixtures is similar to its pure component isotherm. However, for increasing length of the aliphatic chain of the alcohols the adsorption behavior is reversed preventing benzene to be adsorbed. The effect of open metal sites is discarded as main responsible for the preferential adsorption of alcohols, while the entropy and the molecular packing of alcohols are revealed as the reason for the different adsorption behavior of benzene. Abstract : Benzene adsorption in MAF‐6 can be tuned by the presence of small aliphatic alcohols. Increasing chain length of the alcohol (C1‐C3) has a stronger effect on the adsorption of benzene. The molecular packing of 1‐propanol hinders benzene to be adsorbed in the studied structure, reaching an inverse selectivity at high pressure.